Antioxidant Activity of Cubeb Fruit Extract (Piper cubeba L.) Using the ABTS Method and Determining Total Phenolic and Flavonoid Levels - Anggie Kharismatul Mara Salsabila; Anwar, Khoirul; Kiki Damayanti (HM Publisher, 2024)
Cubeb fruit (Piper cubeba L.) is a plant that is rich in flavonoid compounds and has the potential to be a source of natural antioxidants. Free radicals can cause various dangerous diseases. This study aims to determine the antioxidant activity and total flavonoid content of ethanol extract of fruit cubes using the ABTS method. Cubeb fruit is extracted with ethanol using the maceration method. The antioxidant activity of the extract was measured using the ABTS and Trolox methods as a comparison. Total flavonoid levels were determined using the UV-Vis spectrophotometric method using gallic acid and quercetin as a comparison. The total flavonoid content of the ethanol extract of cubed fruit was 3.5302 ± 0.0918 mgQE and the total phenolic content was 183.0396 ± 0.991 mgGAE. The IC50 value of the ethanol extract of cubed fruit was 82.1023 ± 0.072062 µg/mL and trolox 20.1368 ± 0.2367 µg/mL. In conclusion, the ethanol extract of cubed fruit has strong antioxidant activity (IC50 in the range 50-100 µg/mL) and is rich in total flavonoids.